HUBUNGAN PERSEPSI IBU TENTANG DUKUNGAN SUAMI TERHADAP TINGKAT KEBERHASILAN PELAKSANAAN INISIASI MENYUSU DINI (IMD) DI RUMAH SAKIT UMUM DAERAH KOTA YOGYAKARTA - , KOMANG AYU RATNASIH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: According data in 2013, the coverage rate of practice of early breastfeeding initiation in Indonesia in 2010 is 29%, whereas the data of practice of early breastfeeding initiation in Yogyakarta City 2012 show the percentage about 47.9% from 4.658 of live births and perform the early breastfeeding initiation. The implementation of early breastfeeding initiation gives a positive effect for the mother and the infant. As the infant starts sucking the motherâs nipple, there will be two reflexes: prolactin reflex and oxytocin reflex. In the case of the two reflexes, the role of the husband is most needed because those reflexes are affected by the emotional condition of the mother. Support from the husband is one of the sources of social support that is so vital for a woman (wife), especially for breastfeeding practice. Objective: To identify the connection between mothersâ perception about the husband support toward accomplishing level of early breastfeeding initiation in RSUD Kota Yogyakarta. Method: The research is an observational research with designed case control study which conducted on December 2013 until March 2014. Using the observation sheet and questionnaires as the instruments. The result of validity and reliability test of questionnaire is valid of the result is >0,361 with reliability point of 0,934 whereas the observational sheet use the consensus and got the result of 0,9. The subjects of this research are 70 primiparous mothers that have practicing the early breastfeeding initiation. Samples taken with purposive sampling technique. Data analysis with chi square test. Result: In case group there are 25 respondents (71.4%) that have high perception about the husbandâs support and 32 respondents (41.7%) from control group. There is a connection between the motherâs perceptions about husbandâs support with the success rate of implementation of early breastfeeding initiation (p = 0,031 and OR = 4,267). Conclusion: There is a connection between the motherâs perceptions about husbandâs support with the success rate of implementation of early breastfeeding initiation.